Usage of Web Service in Mobile Application for Parents and Students in Binus School Serpong - Karto Iskandar; Andrew Thejo Putranto (Bina Nusantara University, 2016)
A web service is a service offered by a device electronically to communicate with other electronic device using the World wide web. Smartphone is an electronic device that almost everyone has, especially student and parent for getting information about the school. In BINUS School Serpong mobile application, web services used for getting data from web server like student and menu data. Problem faced by BINUS School Serpong today is the time-consuming application update when using the native application while the application updates are very frequent. To resolve this problem, BINUS School Serpong mobile application will use the web service. This article showed the usage of web services with XML for retrieving data of student. The result from this study is that by using web service, smartphone can retrieve data consistently between multiple platforms.